Emmett's dream - Hafner, Marylin (Cricket/McGraw-Hill Columbus, Ohio, 2002)
Molly gets so busy researching her family history for a school project that her cat Emmett feels left out, until Molly tells him about his own famous relatives. Includes suggestions for a genealogy project